Betrixaban is a broad anti-virus inhibitor by activating innate immunity - Hu, Shiyu; Zhao, Yang; Chen, Xingyu; Wang, Haocheng; Hu, Wenjun; Huang, Rong; Yang, Jian; Niu, Chenxi; Guo, Xuefei; You, Fuping (Frontiers in Cellular and Infection Microbiology, 2025)
The innate immune system serves as the first line of defense against viral infections. Type I interferon (IFN-I) signaling, in particular, plays a crucial role in mediating antiviral immunity. Here, we identify Betrixaban (BT), a novel small-molecule compound that activates innate immune responses, leading to broad-spectrum antiviral effects. BT induces IFN-β production and upregulates interferon-stimulated genes (ISGs), effectively suppressing the replication of multiple viruses, including vesicular stomatitis virus (VSV), herpes simplex virus type 1 (HSV-1), murine hepatitis virus strain A59 (MHV-A59), encephalomyocarditis virus (EMCV), and influenza A virus (IAV). BT’s antiviral activity relies on innate immune activation, with IRF3 playing a key role. The antiviral effect was significantly reduced upon loss of ISGs induction, including Mx1 and Mx2. In vivo, BT treatment markedly induced IFNB1 expression across multiple mouse tissues and significantly inhibited viral replication in VSV-infected wild-type mice, confirming the essential role of innate antiviral immune activation. These findings establish BT as a potent stimulator of the innate immune system, demonstrating broad-spectrum antiviral potential and highlighting its promise as a therapeutic agent.